Effect of Rearing Dietary Regimen, Feeder Space and Density on Egg Production, Quality and Size Distribution in Two Strains of Brown Egg Layers - Anderson, K.E.; Jenkins, P.K. (International Journal of Poultry Science, 2011)
Step-Up Protein (SUP) rearing regimens can reduce Feed Consumption (FC) and Body Weight (BW), while still resulting in pullets with equal or superior egg production and egg mass to pullets grown on a Step-Down Protein (SDP) program. Egg weight has been reduced due to SUP programs, presumably due to the reduced BW at sexual maturity. Because BW is reduced by SUP regimens and a slight lowering of FC, BW and EW may be economically advantageous. Therefore, the objective of this experiment was to evaluate the impact of SUP regimens on brown-egg layer rearing program on subsequent productivity and the effect of feeder space and density on performance. Two brown-egg strains, Hy-Line Brown (HB) and the H and N “Brown Nick” (BN) were grown on three different dietary regimens, i.e. a "normal" SDP regimen, a SUP regimen: low energy starter for 9 wk (SUP9) and a SUP regimen: low energy starter for 12 wk (SUP12). The SUP9 and SUP12 feeding regimens resulted in significantly lower BW and feed conversion and shorter sternum length, than the SDP regimen. Egg production was not significantly different among the 3 regimens, but feed conversion was lower while livability was highest in the SUP12 reared hens. Feeder space of 13.6 cm resulted in poorer feed conversion for the SUP12 reared hens. Density per hen of 482 cm2 resulted in significantly improved egg production characteristics, such as 37 more eggs per hen and an 8.1% improvement in flock livability. Only density affected egg income and feed costs and in both egg income and feed costs were higher in hens kept at 482 cm2 were $2.39 and $0.21, respectively. Rearing pullets did not result in a reduced economic return in the laying period, where providing hens a lower density environment increased the per hen income.